CUSTOMS AND TARIFF REGULATION OF IMPORT-EXPORT OPERATIONS IN THE ECONOMIC SECURITY SYSTEM OF UKRAINE - Rudyk, Nataliia; Borodenko, Tetiana; Kostohryz, Yuliia (Current Problems of Sustainable Development, 2026)
Under martial law and the implementation of European integration commitments, the customs and tariff regulation of foreign economic activity becomes a key institutional mechanism for ensuring the economic security of Ukraine. The growing dependence of state budget revenues on customs payments, the structural weakness of the national economy, the raw-material orientation of exports, and the global protectionist transformations make the rethinking of customs policy particularly relevant. The aim of the article is to substantiate the role of customs and tariff regulation of import-export operations in the system of economic security of Ukraine and to develop a conceptual model of their interaction. The study applies a systematic approach, structural-functional analysis, comparative and statistical methods, regression analysis, and SWOT analysis. It is substantiated that customs and tariff regulation simultaneously performs fiscal, regulatory, and protective functions, ensuring the formation of state budget revenues, protection of domestic producers, and integration of the country into the world economy. It is proven that the structure of imports by levels of customs taxation, rather than the gross volume of imports, is the key determinant of customs revenue dynamics: the regression model demonstrates that a one-percentage-point increase in the share of duty-free imports leads to a decrease in customs revenues by approximately UAH 702.2 million. The conducted SWOT analysis of the impact of European integration on customs and tariff regulation revealed both strengths (harmonised legal framework, digital infrastructure, AEO institute) and weaknesses (de jure vs de facto gap, raw-material export structure, institutional weakness), as well as opportunities (single EU market access, re-export potential, VAT deferral model) and threats (global protectionism, CBAM, shadow economy, war-related shocks). The scientific novelty consists in the development of a conceptual model of the relationship between customs and tariff regulation and economic security, integrating fiscal, foreign economic, production, institutional, and innovative-technological dimensions. The practical significance of the results lies in their applicability to the formulation of state customs policy aimed at harmonisation with EU standards while preserving selective tariff protection of strategic sectors of the national economy.